Abstract expressionism - Grosenick, Uta.; Hess, Barbara (Köln Taschen, 2006)
Presents major members of the New York School.
Jackson Pollock -- Arshile Gorky -- Hans Hofmann -- Ad Reinhardt -- William Baziotes -- Philip Guston -- Barnett Newman -- Mark Rothko -- Lee Krasner -- Clyfford Still -- Bradley Walker Tomlin -- Willem de Kooning -- David Smith -- Mark Tobey -- Sam Francis -- Richard Diebenkorn -- Robert Motherwell -- Joan Mitchell -- Helen Frankenthaler -- Adolph Gottlieb -- Franz Kline -- Theodoros Stamos
Keywords: Abstract expressionism -- United States; Painters -- United States